Image Reconstruction Based on Combination of Inverse Scattering Technique and Total Variation Regularization Method - Nor Haizan Jamali; Kismet Anak Hong Ping; Shafrida Sahrani; Dayang Azra Awang Mat; Mohamad Hamiruce Marhaban; Mohd Iqbal Saripan; Toshifumi Moriyama; Takashi Takenaka (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The Forward-Backward Time-Stepping (FBTS) had proven its potential to reconstruct images of buried objects in inhomogeneous medium with useful quantitative information about its size, shape, and locality. The Total Variation regularization method was incorporated with the FBTS algorithm to deal with the ill-posedness or ill-conditionedness of the inverse problem. The effectiveness of the proposed technique is confirmed by numerical simulations. The numerical method was carried out on a simple object detection through FBTS with and without TV regularization method. The detection and reconstruction of relative permittivity and conductivity of the simple object have shown an improvement as TV regularization method applied whereas it smoothed the vibrations of the images and gave a better estimation of the image’s boundaries.